ANALYSIS OF PROJECT TIME AND COST CONTROL WITH CPM, PERT AND CRASHING PROJECT METHODS IN SHOP BUILDING PROJECTS AT CV. MENTARI PERMAI - Rosalinda Rosalinda; Nizmah Nizmah; Suko Ari R; Makmur Makmur; Dian Rarasanti (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Delays in completing the Kelapa Dua shop-house construction project at CV. Mentari permai is a problem that often arises and affects the overall project work. The purpose of this research is to determine the critical path, calculate the costs incurred in the construction of the Kelapa Dua shop-house construction project with the duration of the initial and accelerated work and calculate the percentage of achievement of the shop construction project at CV. Mutia Enchantment of Nature. To overcome these delays, several control methods are used in project management. The methods used in this research are the Critical Path Method, PERT (Program Evaluation and Review Technique) and the Crashing Project. The results of the CPM planning method analysis obtained the project completion time for 91 days from the initial duration of 154 days. Whereas in reality the CPM method, the project completion time is 101 days from the initial duration of 167 days. In the PERT method, the project completion time is 107 days from a duration of 181 days with a probability of completion of 0.62%. And in the crashing project there is an acceleration of the completion duration for 9 days with an increase in costs of Rp. 26,545,194 and a total cost of Rp. 506,613,766.